2019
DOI: 10.1186/s40608-019-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards personalised molecular feedback for weight loss

Abstract: Background Numerous diets, apps and websites help guide and monitor dietary behaviour with the goal of losing weight, yet dieting success is highly dependent on personal preferences and circumstances. To enable a more quantitative approach to dieting, we developed an integrated platform that allows tracking of life-style information alongside molecular biofeedback measurements (lactate and insulin). Methods To facilitate weight loss, participants (≥18 years) omitted one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…This study demonstrated that ACE levels correlate with BMI and weight loss as early as after 1 day of dieting, and thus ACE could be a potential early "biofeedback" marker for weight loss and diet efficiency.Recording of eating patterns through questionnaires with or without computer assistance has been recognized as an effective step in managing obesity [12][13][14]. However, regardless of interface, reporting of too low or too high caloric/energy intake as compared to true intake is a well-documented problem [11,15,16]. This unconscious bias is associated with under-realization and in some scenarios even over-estimation of foods eaten [11,17].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…This study demonstrated that ACE levels correlate with BMI and weight loss as early as after 1 day of dieting, and thus ACE could be a potential early "biofeedback" marker for weight loss and diet efficiency.Recording of eating patterns through questionnaires with or without computer assistance has been recognized as an effective step in managing obesity [12][13][14]. However, regardless of interface, reporting of too low or too high caloric/energy intake as compared to true intake is a well-documented problem [11,15,16]. This unconscious bias is associated with under-realization and in some scenarios even over-estimation of foods eaten [11,17].…”
mentioning
confidence: 99%
“…However, regardless of interface, reporting of too low or too high caloric/energy intake as compared to true intake is a well-documented problem [11,15,16]. This unconscious bias is associated with under-realization and in some scenarios even over-estimation of foods eaten [11,17]. Even if food tracking was entirely accurate, it might not provide sufficient motivation for people to lose weight [11,18].…”
mentioning
confidence: 99%
See 3 more Smart Citations